O sztuce „nieczystej”, różnie rozumianych obrazach i konkurencyjnych modelach ich interpretacji - Stankowska, Agata (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
The paper is devoted to the chosen aspects of varied models of defining the image and research practices created by the contemporary art studies – Visual Culture Studies, anthropologically oriented Bildwissenschaft and the French pictorial semiology. What they all have in common is interdisciplinarity that constitutes a response to the „impurity” of art, trespassing its own borders, being autocritical and exposing not only the artistic, but also political, religious, existential and biological status of the image.